Multi-Criteria Decision Method for Sustainable Watercourse Management in Urban Areas - Priscila Celebrini de Oliveira Campos (Sustainability, 2020)
The rapid urban growth followed by disordered occupation has been generating significant impacts on cities, bringing losses of an economic and social nature that directly interfere with the well-being of the population. In this work, a proposal for local urban infrastructure problems associated with watercourse management is presented, comparing Sustainable Drainage System (SuDS) techniques and Low-Impact Development (LID) concepts with alternative traditional interventions. The study addresses sustainable alternatives to cope with the urbanization of the Cehab’s open channel, which is an important urban watercourse tributary of the Muriaé River, at the municipality of Itaperuna, Rio de Janeiro—Brazil. The multi-criteria decision-making method called Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) was applied here. The results highlighted the better performance of sustainable techniques when compared to the traditional ones, with an overall advantage of the geogrids and geocells for this case study. The obtained TOPSIS coefficients-C for these techniques were higher (0.59488, for Reach 1; and 0.68656, for Reach 2) than those for the others. This research, therefore, presented an important urban watercourse management methodology that can be further applied to guide sustainable investments and help the decision-making associated with the development of territories.